Implementation of BERSABAR Method for Students to Achieve Clean and Healthy Schools in Al Ikhlas Private Elementary School Medan - Tumanggor, Winni R. E.; Chahaya, Indra; Siregar, Cholina Trisa (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Sanitation conditions in the school environment in Urban Village Sitirejo II were not well managed. The school had adequate facilities, but these facilities were not optimally utilized as seen from the unavailability of clean water, unclean toilets, and scattered garbage. These conditions can lead to diseases such as diarrhea and others. The formation of cadres from students needs to be done to overcome these problems. The cadre was named Bocah Cinta Lingkungan or "Bocil" or the Environmentalist Child Cadres, 10 people were selected and formed through "Bersabar" method. The play method used is with the modification of the Snakes and Ladders game, the game is communicative and easy to understand, with eye-catching visualization, attractive, and fun to use as learning media. In addition, snakes and ladders are modified with interesting and full-color illustrated questions and answers. After the cadres are formed, their role is to instill clean and healthy living behaviors for themselves and their peers. Promotive efforts in school children groups can be done with peer education. Furthermore, this program also involves principals and teachers by providing a "Bersabar" method tools to Al Ikhlas Private elemntary School. Teachers have a role to monitor the cadres and then also be able to form the cadres independently.